COMPORTAMENTO TÉRMICO NO PERÍODO DE VERÃO DE EDIFICAÇÃO EDUCACIONAL LOCALIZADA NA ZONA BIOCLIMÁTICA BRASILEIRA 2 - Lourenço, Willian Magalhães de; Woloszyn, Maraysa; Garlet, Liege; Ruviaro, Raiana; Pizzutti, Joaquim (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Understanding the climatic impacts and the advancement of technology in civil construction provides a reflection on the conditions of thermal comfort in buildings and their own performance. Therefore, this study promotes the analysis of summer thermal flows for a school building located in the City of Santa Maria, Brazilian Bioclimatic Zone 2, proposing solutions to soften the thermal gains. Through computer simulation with the EnergyPlus software and the help of the graphical interface of Sketchup Make and OpenStudio, thermoenergetic simulations of the building were realized and analyzed the most critical environment from the thermal point of view. Flow analysis showed that the greatest heat gains were from transparent and opaque closures. Among the opaque closures, the roof of the building and the west wall stand out. Solutions were proposed to these gains, based on the requirements stipulated by the norms of thermal performance of buildings, which present constructive guidelines for each Bioclimatic Zone. The results found are important for the decision making of the construction professionals, as well as for the reflection of their role as designers.